How did the 2012 drought affect rural livelihoods in vulnerable areas? Empirical evidence from India. (September 2015) - Udmale, Parmeshwar D.; Ichikawa, Yutaka; Manandhar, Sujata; Ishidaira, Hiroshi; Kiem, Anthony S.; Shaowei, Ning; Panda, Sudhindra N.
Abstract: This study identifies the severity of impacts of drought in 2012 on domestic water supply, crop production, unskilled rural employment, and financial status of rural households in a drought-prone area of India. It is based on secondary and primary data collected by interviewing 223 households. The data were analyzed using descriptive and inferential applications in SPSS. As a consequence of drought, access to domestic water supply was cumbersome and time spent on water collection activities almost doubled compared with the time required in years with normal rainfall. On average, a respondent household suffered a loss of about 86% in production of major crops. High reductions in on-farm unskilled employment opportunities and an increase in unskilled labor in off-farm rural employment activities were reported. It was found that about 69% of respondents were availing loans and 79% of them delayed repayment of loans due to the consequences of drought. Our results indicated that the extent of drought damage varied according to household size, annual income, landholding size, farming system in use, and drought intensity. The effects of these factors on farming communities are reported with empirical evidence. Respondents with large family size, low to marginal land holding size, low income, and rainfed farming systems are found to be more vulnerable to drought impacts; special attention should be given towards increasing their resilience when designing drought management strategies.